2016
DOI: 10.1002/rem.21458
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Sustainable Soil Remediation—Case Study Suggests Novel Fungal Genera Could Facilitate in situ Biodegradation of Hazardous Contaminants

Abstract: Deciding upon a cost effective and sustainable method to address soil pollution is a challenge for many remedial project managers. High pressure to quickly achieve cleanup goals pushes for energy-intensive remedies that rapidly address the contaminants of concern with established technologies, often leaving little room for research and development especially for slower treatment technologies, such as bioremediation, for the more heavily polluted sites. In the present case study, new genomic approaches have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
(40 reference statements)
1
8
0
1
Order By: Relevance
“…The wood treatments did not stimulate anthracene removal significantly over the control (p>0.05). This result is consistent with the limitations observed in previous wood-based mycostimulation tests in polluted soils [50] and also explains the persistence of woodchips in contaminated media also piled on the site where samples were collected [19]. …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The wood treatments did not stimulate anthracene removal significantly over the control (p>0.05). This result is consistent with the limitations observed in previous wood-based mycostimulation tests in polluted soils [50] and also explains the persistence of woodchips in contaminated media also piled on the site where samples were collected [19]. …”
Section: Resultssupporting
confidence: 91%
“…Reactors were set up to test the influence of three amendments (cellulose, chitin, and wood substrates) supplied at two different concentrations (0.1% and 1% w/v) on the degradation of anthracene introduced at three concentrations (0.4 mg/L, 4mg/L, and 40 mg/L). Anthracene was selected as the model PAH as it tends to be ubiquitous at PAH contaminated sites and has been well studied previously [19, 24, 25]. Carbon amendments were selected to mimic the substrates used by fungi in natural ecosystems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of indigenous fungi could provide the best candidate organisms for bioremediation of polluted soil since they already belong to an established soil microbial community and may be adapted to the site conditions (Czaplicki et al 2016). For example, Srivastava and Thakur (2006) Coprinus comatus on a soil affected by cadmium and an organic pollutant (endosulfan).…”
Section: Methods To Evaluate the Effects Of Metals On Fungal Aerobic mentioning
confidence: 99%
“…The potential of fungi to tolerate and transform both organic and inorganic pollutants has been highlighted in many studies which have also reported some unusual abilities shown by fungi isolated from contaminated soil (;Tigini et al 2009;Ma et al 2014;Mishra and Malik 2014). In fact, isolation of indigenous fungi could provide the best candidate organisms for bioremediation of polluted soil since they 3 already belong to an established soil microbial community, and are best adapted to the site conditions (Czaplicki et al 2016).…”
Section: Introductionmentioning
confidence: 99%